2016
DOI: 10.1017/s0272263116000243
|View full text |Cite
|
Sign up to set email alerts
|

L2 Selves, Emotions, and Motivated Behaviors

Abstract: This study has aimed to investigate language learners’ emotional experiences through the lens of L2 future self-guides. To that end, the L2 motivational self system was chosen as the theoretical framework to relate learners’ emotions to their L2 selves. However, due to inconsistent results of past research concerning the motivational role of the ought-to L2 self, a revision of the model is proposed, discussed theoretically, and tested empirically. The results revealed a trichotomous model of L2 selves—ideal L2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
207
8
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 208 publications
(256 citation statements)
references
References 64 publications
(114 reference statements)
19
207
8
3
Order By: Relevance
“…As such, their greater motivational configurations elicit not only more enjoyment but also less anxiety about EFL learning. In line with the recent motivation and emotion literature (Papi & Teimouri, ; Teimouri, ), our findings echo those that have shown that having strongly internalized motivation (Ideal L2 Self) evokes various kinds of emotion (anxiety, enjoyment).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…As such, their greater motivational configurations elicit not only more enjoyment but also less anxiety about EFL learning. In line with the recent motivation and emotion literature (Papi & Teimouri, ; Teimouri, ), our findings echo those that have shown that having strongly internalized motivation (Ideal L2 Self) evokes various kinds of emotion (anxiety, enjoyment).…”
Section: Discussionsupporting
confidence: 92%
“…As such, their greater motivational configurations elicit not only more enjoyment but also less anxiety about EFL learning. In line with the recent motivation and emotion literature (Papi & Teimouri, 2014;Teimouri, 2016), our findings echo those that have shown that having strongly internalized motivation (Ideal L2 Self) evokes various kinds of emotion (anxiety, enjoyment). In response to the first research question concerning the interaction patterns between L2 learners' motivation and emotion factors and their experience, our cross-sectional and longitudinal analyses demonstrated that both Ideal L2 Self and Ought-to L2 Self demonstrated small-to-medium correlations with various stages of the participants' experience at preschool, junior high school, and high school (r = .20-.30), indicating that motivation is closely aligned with L2 learners' behaviors relating to studying, using, and practicing the target language throughout their EFL experience (Dörnyei, 2009;Ushioda, 2016).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This points to the urgent need for further psychometric research to refine scales that are frequently cited in the L2 motivation literature. Several novel lines of research have begun to do this (e.g., Papi, Bondarenko, Mansouri, Feng, & Jiang, ; Teimouri, ).…”
Section: Discussionmentioning
confidence: 99%
“…Teimouri () also examined shame experiences of L2 learners within Dörnyei's L2 motivational self system (Dörnyei, ). The results of a survey of 524 Iranian students of English as a foreign language (EFL) revealed that all L2 learners, regardless of their motivational types (ideal L2 self vs. ought‐to L2 self), are susceptible to some extent to the emotional reaction of shame—although those students with stronger social and personal obligations for learning English (i.e., ought‐to L2 self/others and ought‐to L2 self/own) were found to be more vulnerable to feelings of shame.…”
Section: L2 Learners’ Feelings Of Shame and Guiltmentioning
confidence: 99%